Seminal Bacterioflora of Two Rooster Lines: Characterization, Antibiotic Resistance Patterns and Possible Impact on Semen Quality - Tvrdá, Eva; Petrovičová, Michaela; Benko, Filip; Ďuračka, Michal; Kováč, Ján; Slanina, Tomáš; Galovičová, Lucia; Žiarovská, Jana; Kačániová, Miroslava (Antibiotics (Basel), 2023)
This study aimed to characterize the bacterial profiles and their association with selected semen quality traits among two chicken breeds. Thirty Lohmann Brown and thirty ROSS 308 roosters were selected for semen quality estimation, including sperm motility, membrane and acrosome integrity, mitochondrial activity, and DNA fragmentation. The oxidative profile of the semen, including the production of reactive oxygen species (ROS), antioxidant capacity, protein, and lipid oxidation, were assessed as well. Moreover, the levels of pro-inflammatory cytokines, including tumor necrosis factor alpha (TNF-α), interleukins 1 and 6 (IL-1, IL-6) and C-reactive protein, as well as the concentrations of selected antibacterial proteins (cathelicidin, β-defensin and lysozyme) in the seminal plasma were evaluated with the enzyme-linked immunosorbent assay. The prevailing bacterial genera identified by the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry were Citrobacter spp., Enterococcus spp., Escherichia spp. and Staphylococcus spp. While the bacterial load was significantly higher in the ROSS 308 line (p < 0.05), a higher number of potentially uropathogenic bacteria was found in the Lohmann Brown roosters. Antimicrobial susceptibility tests revealed a substantial resistance of randomly selected bacterial strains, particularly to ampicillin, tetracycline, chloramphenicol, and tobramycin. Furthermore, Lohmann Brown ejaculates containing an increased proportion of Escherichia coli presented with significantly (p < 0.05) elevated levels of TNF-α and IL-6, as well as ROS overproduction and lipid peroxidation. Inversely, significantly (p < 0.05) higher levels of β-defensin and lysozyme were found in the semen collected from the ROSS 308 roosters, which was characterized by a higher quality in comparison to the Lohmann Brown roosters. In conclusion, we emphasize the criticality of bacteriospermia in the poultry industry and highlight the need to include a more complex microbiological screening of semen samples designated for artificial insemination.